2016
DOI: 10.1080/01443410.2016.1176125
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effect of a teacher training programme on the primary teachers’ attitudes, knowledge and teaching strategies regarding special educational needs

Abstract: Faculty of Psychology, universitas indonesia, depok, indonesia; b department of special needs Education and youth care, university of groningen, groningen, the netherlands Including students with special educational needs (SEN) in regular classrooms has become a global trend. International policies have continually strived for the inclusion of such students, starting with the Warnock report (1979) and followed by the Salamanca statement (UNESCO, 1994). Most recently, Article 24 of the UN Convention on the Righ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 33 publications
(32 reference statements)
1
32
0
11
Order By: Relevance
“…According to Ramadani et al (2014), attitude is positively related to behavioral intention. A more comprehensive definition by Kurniawati et al (2017) describes that an attitude is a person's view or character which affective, cognitive, and behavioral components, and the cognitive constituent is one's beliefs or information about the attitude object. Onur et al (2000) brief that understanding the relatives between cognitive construction (i.e., beliefs), affect, and attitude has been the emphasis of attitude research.…”
Section: Attitudesmentioning
confidence: 99%
“…According to Ramadani et al (2014), attitude is positively related to behavioral intention. A more comprehensive definition by Kurniawati et al (2017) describes that an attitude is a person's view or character which affective, cognitive, and behavioral components, and the cognitive constituent is one's beliefs or information about the attitude object. Onur et al (2000) brief that understanding the relatives between cognitive construction (i.e., beliefs), affect, and attitude has been the emphasis of attitude research.…”
Section: Attitudesmentioning
confidence: 99%
“…Most had the educational level of a Bachelor's degree (95.5%). In this research, teachers' instructional support was measured using the Instructional Support instrument developed by Author [7], [details removed for peer review]. This instrument is the product of the Classroom Assessment Scoring System (CLASS) by Allen, Gregory, Mikami, Lun, Hamre, & Pianta, 2013).…”
Section: Methodolgymentioning
confidence: 99%
“…In Indonesia's, the implementation of inclusive education faced some challenges, primarily from the teachers charged with carrying out inclusive education as well as those who make changes in the classroom teaching process [5]. Many teachers stated that these changes are not easy because they are not ready to manage their classroom in inclusive setting [6] or to give the required instructional support [7] [details removed for peer review]. Schumm and Vaughn, in Emmer [6], found that only 39% of teachers were ready to run an inclusive classroom.…”
Section: Introductionmentioning
confidence: 99%
“…However, that particular study evinced some limitations. Kurniawati et al (2016) and Srivastava et al (2015), found, on the contrary, that teachers who participated in a training program became more knowledgeable about students with SEN and about inclusive schooling. These studies found that the cognitiveaffective components of the attitudes of such teachers also improved significantly.…”
Section: Introductionmentioning
confidence: 96%
“…The training program accorded teachers of inclusive schools the opportunity to receive specialized training on inclusive education and special needs training strategies. The effects of the SERASI training program on the attitudes of the teachers were measured using the Multidimensional Attitudes Toward Inclusive Education Scale (MATIES) adapted from Marian Mahat's original version (2008) and developed by Farida Kurniawati (2016). This instrument has been proved to be reliable.…”
Section: Introductionmentioning
confidence: 99%